2016
DOI: 10.1093/eurheartj/ehw284
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in patients treated with ticagrelor or clopidogrel after acute myocardial infarction: experiences from SWEDEHEART registry

Abstract: Ticagrelor vs. clopidogrel post-ACS was associated with a lower risk of death, MI, or stroke, as well as death alone. Risk of bleeding was higher with ticagrelor. These real-world outcomes are consistent with randomized trial results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
112
1
11

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(142 citation statements)
references
References 28 publications
(24 reference statements)
18
112
1
11
Order By: Relevance
“…The PLATO study showed that ticagrelor is a more effective drug for the [2]. Similar results were reported by other studies [28,29]. However, its effect has not yet been proven for pre-PCI coronary reperfusion in a group of patients with acute STEMI following ticagrelor treatment [26].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The PLATO study showed that ticagrelor is a more effective drug for the [2]. Similar results were reported by other studies [28,29]. However, its effect has not yet been proven for pre-PCI coronary reperfusion in a group of patients with acute STEMI following ticagrelor treatment [26].…”
Section: Discussionsupporting
confidence: 76%
“…Compared with clopidogrel, ticagrelor is a more effective drug for decreasing platelet aggregation and the prevention of arterial thrombosis, such as definite stent thrombosis; this is because it has a more beneficial mechanism of action than clopidogrel [29], and it does not require metabolic activation. On the other hand, it may cause more bleeding events [2,28,35]. Thus, one of the aims of our study was to identify genetic and nongenetic factors which may significantly affect the antiplatelet therapy of ticagrelor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The real life experience of ticagrelor was evaluated in SWEDEHEART registry 42 . This non-randomized prospective cohort study of 45,073 ACS patients in Sweden demonstrated amplified benefits of ticagrelor in comparison with clopidogrel.…”
Section: N/a= Not Applicablementioning
confidence: 99%
“…Например, в шведском регистре SWEDHEART выявлено, что после острого ИМ частота суммы неблаго-приятных событий (смерть, ИМ, инсульт) через 24 месяца у пациентов, принимавших тикагре-лор, была 11,7%, а у принимавших клопидог-рел -22,3%, а частота кровотечений, потребо-вавших госпитализации, была сравнимой -5,5 и 5,2% соответственно [14].…”
Section: рисунок 2 схема периоперативного подхода к дат у пациентов unclassified